2021
DOI: 10.1007/s11116-021-10230-3
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating psychological needs in commute mode choice modelling: a hybrid choice framework

Abstract: This study proposes an integrated choice and latent variable model (ICLV) for commute mode choice that incorporates satisfaction of human needs and perceived functional and psychological barriers to using certain modes. The modelling framework is validated by data from a survey of commuters in the Greater Copenhagen area, which has large numbers of car users, public transport riders and bicyclists. The model results suggest that higher bicycle use is correlated to positive cycling self-concepts. Similarly, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Hergesell and Dickinger (2013) suggested that encouraging general pro-environmental behaviors while improving citizens' environmental awareness can more efficiently promote green transport than traditional market-based interventions that considered various transport modes in terms of price, time, and convenience. Ingvardson et al (2021) suggested that a traveler's self-concept/identity/esteem (a general term used to refer to how someone thinks about, evaluates, or perceives themselves) is highly related to daily travel mode choice. Aaditya and Rahul (2021) suggested that because of the Covid-19 pandemic, social distancing, masks, and personal sanitization have become the new lifestyle standards that significantly affect people's travel mode choices.…”
Section: Attitude and Lifestylementioning
confidence: 99%
“…Hergesell and Dickinger (2013) suggested that encouraging general pro-environmental behaviors while improving citizens' environmental awareness can more efficiently promote green transport than traditional market-based interventions that considered various transport modes in terms of price, time, and convenience. Ingvardson et al (2021) suggested that a traveler's self-concept/identity/esteem (a general term used to refer to how someone thinks about, evaluates, or perceives themselves) is highly related to daily travel mode choice. Aaditya and Rahul (2021) suggested that because of the Covid-19 pandemic, social distancing, masks, and personal sanitization have become the new lifestyle standards that significantly affect people's travel mode choices.…”
Section: Attitude and Lifestylementioning
confidence: 99%